2015
DOI: 10.1139/cjm-2015-0156
|View full text |Cite
|
Sign up to set email alerts
|

Screening of ligninolytic fungi for biological pretreatment of lignocellulosic biomass

Abstract: https://mc06.manuscriptcentral.com/cjm-pubs In order to identify white rot fungi with high potential in biological pretreatment of lignocellulosic biomass, 18 preliminary screening was carried out on plates by testing strains' abilities to oxidize guaiacol and decolorize the 19 dyes, azure B and Poly R-478. Of the eighty six strains screened, sixteen were further used for secondary screening 20 based on their ligninolytic ability. However, low manganese peroxidase activity and no lignin peroxidase activity 21 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…It can be observed that from eight lignocellulosic biomasses, corn stover presented the highest lignin delignification and lowest total weight loss which is reflected in a higher lignin selectivity removal; while it obtained the second highest results of final holocellulosic digestibility, after wheat straw. In a previous study, in which 33 strains of WRF were evaluated on three lignocellulosic biomasses (bamboo, rice straw and corn stover) it was found that Irpex lacteus was the fungus that produced the highest saccharification rates after 15 d of fungal pretreatment (Xu et al, 2009).…”
Section: Biological Pretreatmentmentioning
confidence: 98%
“…It can be observed that from eight lignocellulosic biomasses, corn stover presented the highest lignin delignification and lowest total weight loss which is reflected in a higher lignin selectivity removal; while it obtained the second highest results of final holocellulosic digestibility, after wheat straw. In a previous study, in which 33 strains of WRF were evaluated on three lignocellulosic biomasses (bamboo, rice straw and corn stover) it was found that Irpex lacteus was the fungus that produced the highest saccharification rates after 15 d of fungal pretreatment (Xu et al, 2009).…”
Section: Biological Pretreatmentmentioning
confidence: 98%
“…MnP producing strains were detected by inoculating fungal mycelia on basal salts medium containing 0.01% guaiacol as described previously [11]. After 24 days culture, the MnP producing strains were confirmed by a halo to colony ratio of oxidized guacicol around the fungal colonies.…”
mentioning
confidence: 99%
“…The utilization of sole carbon and nitrogen sources, decomposition of cellulose, hydrolysis of starch and aesculin, reduction of nitrate, coagulation of milk, liquefaction of gelatin and production of H 2 S were examined as described previously (Gordon et al 1974;Yokota et al 1993). The ability of lignin degradation was determined by the azure B plate decolorization method (Xu et al 2015).…”
Section: Phenotypic Characteristicsmentioning
confidence: 99%